Rumichaca : Un puente inca en la cordillera de Los Chicas (Tarija, Bolivia) - Raffino, Rodolfo Adelio; Methfessel, C.; Vitry, C.; Gobbo, Diego
mapas; fot. col.
pp. 61-71
Keywords: Incas; Excavaciones Arqueologicas; Tarija; Charcas; Arqueología; Bolivia